ДУХОВНИЙ КОНТЕКСТ МОДУЛЬНО-РОЗВИВАЛЬНОЇ СИСТЕМИ НАВЧАННЯ, ВИХОВАННЯ Й ОСВІТИ (Педагогіка вищої та середньої школи, 2007)
The article deals with the issues harmonious unity of spiritual context of modular-developing system, fundamental value of culture and education, valuable modular-developing process and teachers professional readiness.